Strategi Pengembangan Kelompok Tani Menuju Kemandirian (Kasus Kelompok Maroha Di Desa Sigapiton Kecamatan Ajibata, Kabupaten Toba-Samosir) - SITINJAK, JEREMIA M.; PUTRA, I GEDE SETIAWAN ADI; SARJANA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.1, Juli 2023DO - 10.24843/JAA.2023.v12.i01.p23, 2023)
Farmer Group Development Strategy Towards Independence (Case of Maroha Farmer Group in Sigapiton Village, Ajibata District, Toba-Samosir Regency) Maroha Farmer Group is one of the farmer groups in Sigapiton Village, Ajibata District, Toba Samosir Regency. The purpose of this study was to analyze (1) the internal factors contained in determining the empowerment strategy of the Maroha Farmer Group in Sigapiton Village, Ajibata District, Toba-Samosir Regency. (2) the external factors contained in determining the empowerment strategy of the Maroha Farmer Group in Sigapiton Village, Ajibata District, Toba-Samosir Regency and (3) to be able to analyze the development strategy towards independence of the Maroha Farmer Group in Sigapiton Village, Ajibata District, Toba- Samosir. The population in this study were members of the Maroha Farmer's Group in Sigapiton Village, amounting to 142 people, while the number of samples was 34 members of the Maroha Farmer Group in Sigapiton Village who became respondents. In formulating a strategy for developing the independence of the Maroha Farmer Group using a SWOT analysis. The results of the study found that in developing the independence of farmer groups, special attention was needed from all parties in carrying out each plan. Of course, it will help implement and control the programs and problems that exist in the farmer groups. Full encouragement is needed for the involvement of every stakeholder to increase farmer productivity developed in the Farmer Group. farmer groups need to carry out ideas in land management, the utilization of the funding budget that is calibrated and implemented as effectively as possible. It aims to be able to increase the income of farmers. The budgeted funding would be able to help farmers' productivity in improving land management, the availability of information and counseling about pests, distribution channel management also needs to be considered.